PENGARUH STRESS KERJA, KOMPENSASI, DAN PELATIHAN BODY REPAIR OTOMOTIF TERHADAP KINEJRA MONTIR DI BADAN USAHA R HOUSE AUTODETAILING - Barki Muhammad Riski Helmy, (2022)
This research was conducted with the aim of testing the effect of work stress, compensation and training on employee performance empirically. In this study, the independent variables are work stress, compensation and training. With performance as the dependent variable. The type of research used is quantitative research. The sample used is a mechanic at the R.house business entity using a sampling technique, a saturated sample technique which means that the entire population is used as a sample. Respondent data was obtained by questionnaires which were distributed directly to 32 mechanics. The data analysis technique used is the t test and the coefficient of determination using the SmartPLS 3.0 software and the F (simultaneous) test manually. The results of this study stated that a significant effect was found in the relationship between work stress and performance, in the relationship between compensation and performance there was no significant effect. It was found that there was a significant effect between training and performance and also job stress, compensation and performance had a significant effect simultaneously on performance.